Overuse or underuse? Use of healthcare services among irregular migrants in a north-eastern Spanish region - Luis Andrés Gimeno-Feliu; Marta Pastor-Sanz; Beatriz Poblador-Plou; Amaia Calderón-Larrañaga; Esperanza Díaz; Alexandra Prados-Torres (BMC, 2021)
Abstract Background There is little verified information on global healthcare utilization by irregular migrants. Understanding how immigrants use healthcare services based on their needs is crucial to establish effective health policy. We compared healthcare utilization between irregular migrants, documented migrants, and Spanish nationals in a Spanish autonomous community. Methods This retrospective, observational study included the total adult population of Aragon, Spain: 930,131 Spanish nationals; 123,432 documented migrants; and 17,152 irregular migrants. Healthcare utilization data were compared between irregular migrants, documented migrants and Spanish nationals for the year 2011. Multivariable standard or zero-inflated negative binomial regression models were generated, adjusting for age, sex, length of stay, and morbidity burden. Results The average annual use of healthcare services was lower for irregular migrants than for documented migrants and Spanish nationals at all levels of care analyzed: primary care (0.5 vs 4 vs 6.7 visits); specialized care (0.2 vs 1.8 vs 2.9 visits); planned hospital admissions (0.3 vs 2 vs 4.23 per 100 individuals), unplanned hospital admissions (0.5 vs 3.5 vs 5.2 per 100 individuals), and emergency room visits (0.4 vs 2.8 vs 2.8 per 10 individuals). The average annual prescription drug expenditure was also lower for irregular migrants (€9) than for documented migrants (€77) and Spanish nationals (€367). These differences were only partially attenuated after adjusting for age, sex, and morbidity burden. Conclusions Under conditions of equal access, healthcare utilization is much lower among irregular migrants than Spanish nationals (and lower than that of documented migrants), regardless of country of origin or length of stay in Spain.